(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Companion diagnostics (CDx) are vital in personalized medicine because they help find patients who would benefit the most from specific treatments. The rules for these tests can be different depending on where you are, which affects how easily they can be used and developed. In the U.S., the FDA has a clear process for approving CDx on the same path as the therapies they relate to. Over in Europe, they recently made their regulations stricter with the In Vitro Diagnostic Regulation (IVDR), which means more requirements for proof and oversight. Even though there are efforts to make things more uniform, the differences in approval times, data needs, and who gets reimbursed can make it tricky to roll out CDx globally. This review looks at these varying rules and how they impact developing and using CDx. CDx has become essential in treating conditions like cancer, cystic fibrosis, and asthma. In cancer, for instance, CDx helps identify genetic issues that can lead to better treatment options. For cystic fibrosis, CDx is useful in picking the right modulators for improved patient results. In asthma, new CDx methods focus on biomarkers to customize treatments. But there are hurdles, like varying approval paths in the U.S., stricter regulations in Europe needing more proof and monitoring, and challenges in getting reimbursement. There’s also a need to consider genetic differences and acceptance of CDx outside of oncology. To really expand the benefits of CDx for different diseases, it’s important to work on more streamlined regulations, inclusive studies, and flexible approval paths.